Hydrothermal synthesis and characterisation of α-Fe2O3 nanorods - Almeida, Trevor P. (2010)
The hydrothermal synthesis (HS) of α-Fe2O3 nanorods (NRs) is investigated using a combination of complementary analytical techniques. The construction of an HS ‘process map’ as a function of temperature, time and phosphate (PO43-) concentration provides insight into the nature of intermediate β-FeOOH NR precipitation, dissolution and subsequent α-Fe2O3 growth, along with the effect of PO43- anion concentration on the development of α-Fe2O3 particle shape. An HS processing temperature of 200˚C and an Fe3+ : PO43- molar ratio of 31.5 yielded crystalline acicular α-Fe2O3 NRs with an aspect ratio of ~ 7 (~ 420 nm long, ~ 60 nm wide). The additional effects of FeCl3 concentration, pH, stage of phosphate addition and α-Fe2O3 seed content on the growth of α-Fe2O3 NRs is investigated.